Hybrid reinforcement of TRC from flax and AR glass - Jakub Hájek; Matthew Schwarzkopf; Marica Mikuljan; Tomáš Vlach (Acta Polytechnica CTU Proceedings, 2025)
This article focusses on the possible use of hybrid reinforcement from inorganic and organic materials in a thin concrete plates, such as Textile-reinforced concrete. Organic materials, such as flax, jute, or sisal, have high tensile strengths. Young’s modulus is, on the other hand, problematic, so the combination with inorganic textiles goes hand in hand. Natural fibres are renewable materials, making them an environmentally friendly material, so using them as a partial substitution of inorganic materials would make concrete reinforcement more sustainable. In this article, four-point tests of hybrid reinforced concrete plates with alkali-resistant glass and flax are presented. In addition, a hybrid reinforcement cross-sectional microscopy was done to evaluate the impregnation with epoxy resin.